Comparison of outcomes following transplantation with T-replete HLA-haploidentical donors using post-transplant cyclophosphamide to matched related and unrelated donors for patients with AML and MDS aged 60 years or older. (June 2018) - Bashey, Zain; Zhang, Xu; Brown, Stacey; Jackson, Katelin; Morris, Lawrence; Holland, H.; Bashey, Asad; Solomon, Scott; Solh, Melhem
Abstract Allografting from HLA-haploidentical donors (HID) is being increasingly utilized worldwide for patients lacking a conventional matched donor. However, its efficacy in older patients with AML and MDS is unclear. We analyzed 127 consecutive allografts for AML/MDS patients aged ≥ 60 years at our center to compare outcomes using HID to those of contemporaneous transplants using matched sibling (MRD) or matched unrelated (MUD) donors. Patient characteristics were similar except HID transplants were more likely in non-white patients and were more commonly performed with reduced intensity conditioning and a marrow graft. For MRD, MUD and HID transplants respectively, 2-year estimates of non-relapse mortality (17, 23, and 9%), relapse (32, 34, and 33%), overall survival (OS) (62, 55, and 67%) and disease-free survival (DFS) (51, 43, and 58%) were not significantly different. Maximum cumulative incidences of grade 2–4 acute GVHD were not different (27, 37, 39%), but incidences of NIH grade moderate to severe (39, 35, 15%, p = 0.028 MUD vs. HID, p = 0.026 MRD vs. HID) and severe chronic GVHD (9, 12, 0%, p = 0.030 MUD vs. HID, p = 0.009 MRD vs. HID) were significantly higher in MRD and MUD than in HID transplants. On multivariable analysis, donor type was not a significant determinant of OS, DFS, TRM, or relapse. However, male gender and high/very high Disease Risk Index (DRI) were associated with significantly higher rates of relapse (HR 1.94, p = 0.047 for male gender, HR 2.48, p = 0.004 for high/very high DRI) and lower OS (HR 1.94, p = 0.018 for male gender, HR 1.80, p = 0.025 for high/very high DRI). HIDs are an acceptable alternative to matched donors in older patients with AML and MDS.